Performance evaluation of stepped multiple basin pyramid solar still. (2021) - Prakash, A.; Jayaprakash, R.
Abstract: In this work an attempt has been carried out to design and construct a novel stepped multiple basins in pyramid solar desalination system. Four basins have been incorporated in the pyramid solar still in which the area of each basin varies gradually towards the condensing glass surface. The stepped basins have reduced the thermal capacity due to the decrease of surface area of the evaporating surface facing the condensing glass surface. Energy balance equations for the proposed still has been written for temperature components and solved for the analytical solutions to determine the thermal performance. The theoretical results are found to be in well agreed with the experimental observations. The efficiency of the proposed pyramid solar desalination system is found to be 50.85% on average with an average distillate yield of 3.25 l/day including night time collection.